History of the dukes of Normandy and the kings of England by the Anonymous of Béthune
1 online resource.
Keywords: "In the first quarter of the thirteenth century, an anonymous Flemish writer set in writing, in Old French, a chronicle of Normandy, England, Flanders and northern France. It ranged from the arrival of the Vikings in Normandy to the early years of the reign of King Henry III of England, ending with an account of the translation of the relics of St Thomas Becket to their magnificent new shrine in Canterbury Cathedral in 1220. Along the way, it adopted and formed part of a tradition of writing of the history of the dukes of Normandy and kings of England, a tradition which had developed in Latin in the eleventh and twelfth centuries, and then continued in Old French. The work is famous for vibrant and informed description of the reign of King John, in particular the period of baronial reaction, Magna Carta, ensuing civil war and the nearly-successful invasion of England by Louis, heir to the kingdom of France. Flanders supplied troops to both sides, and this Flemish author sees these events in close detail, and from the Flemish, not the French or English, point of view. He may himself have been an eyewitness, directly involved, but if not he would have known many who had fought and died in this conflict. Janet Shirley's translation of this chronicle, the first into English, brings the work of the Anonymous of Béthune to a new audience in this volume, accompanied by an introduction and historical notes by Paul Webster"--